MONITORING AKTIVITAS PRODUKSI MACHINING DENGAN PEMANFAATAN FRAMEWORK CODEIGNITER - Sandi Ahmad; Bayu Priatna; Tukino Tukino; Saepul Aripiyanto (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
PT XYZ is a company in the automotive industry that produces wheels for cars and motorcycles. Many production activity reports use Microsoft Office Excel, which causes errors in data processing. The data processing process in the production activity report still takes a long time because it is not supported by a computer system. Given these problems, there must be a reporting of production activities to overcome problems at PT XYZ. The aim of this research is to make reports on production activities using the codeigniter framework, by processing production activity report data in a monitored and systematic way, a proper daily production activity report will be produced. It is hoped that the results of the research in the form of production activity reports will provide convenience for processing production data from daily reporting to monthly reports, then presenting production activity data reports to PT XYZ can be stored in the database, so that it is expected to speed up data retrieval.